A Critical Review of the Properties and Analytical Methods for the Determination of Curcumin in Biological and Pharmaceutical Matrices. (4th March 2019) - Carolina Alves, Renata; Perosa Fernandes, Richard; Fonseca-Santos, Bruno; Damiani Victorelli, Francesca; Chorilli, Marlus
Abstract: Curcumin, a natural compound extracted from turmeric ( Curcuma longa ), has been extensively studied because of its various pharmacological properties, such as anti-inflammatory, antioxidant, antibiotic, antiprotozoal, immunomodulatory, anti-proliferative, antitumor, and anticarcinogenic effects. However, low solubility in aqueous media has limited its therapeutic applications. To overcome these bioavailability issues, the use of drug delivery systems providing localized or targeted delivery of this drug may represent a more viable therapeutic option. Several drug delivery systems have been shown to significantly enhance the therapeutic efficacy of curcumin. Additionally, a wide variety of analytical methods are available for the qualitative and quantitative analysis of curcumin in different matrices, including plant extracts, biological fluids, and drug delivery systems. There are a variety of methodologies to quantify curcumin, but chromatographic and spectroscopic techniques are the ones most commonly used. Thus, in this review, we evaluate the biological properties of curcumin, as well as its nanotechnology-based delivery systems and methods of analysis.